A method of producing a composition comprising calcium aluminate - Pavia, Sara (European (EPO) Patent Application, 2025)
The present invention relates to method of producing a composition comprising calcium aluminate. Also disclosed are compositions comprising calcium aluminate obtained from the methods and their use as binders, cements, and in concretes. Also disclosed are articles comprising the compositions comprising calcium aluminate, which can find utility as construction commodities such as bricks, tiles, blocks, and other refractory materials.
GRANTED
Keywords: Cement and Concrete Chemistry; Civil Engineering, Pavements and Structures; Composite materials; Design Engineering; Materials Engineering; Materials, Physical Properties; low carbon cement; low carbon materials; Other; Environment and housing